PERLINDUNGAN HUKUM BAGI NASABAH PERUSAHAAN PERGADAIAN (Faculty of Law, University of Dr. Soetomo, 2019)
Preventive legal protection for customers of pawnshop company has been adequately regulated in the Financial Services Authority Regulations, namely regarding the requirements for legal entity forms, ownership and capital. In addition, there are restrictions that must be obeyed by pawnshop company as a form of protection for customers. Whereas repressive protection is a dispute resolution mechanism through the settlement of complaints made by the pawnshop company and dispute resolution through a court or an outside judicial institution, namely through an alternative dispute resolution institution.Keywords: Protection, customers, pawnshop company